All-in-one surgical guide: A new method for cranial vault resection and reconstruction. Issue 6 (June 2018) - Tel, Alessandro; Costa, Fabio; Sembronio, Salvatore; Lazzarotto, Andrea; Robiony, Massimo
Abstract: Introduction: Great precision is required for craniofacial surgery, and computer-aided design (CAD) methods may be used to plan surgery before it is performed. In this study, three-dimensional (3D)-printed cutting guides are used to match computer models with surgical procedures. We describe a novel method of computer-aided surgery for autologous cranioplasty that includes a new strategy for generating and using cutting guides. These guides may be used not only for osteotomies, but also for many other steps in the surgical procedure. Materials and methods: Preoperatively, anatomical data were imported into a CAD package and used for virtual surgical planning (VSP). Cutting guides were designed after considering how to integrate all the surgical steps. Models of the microplates and micro-screws were also made. Surgical guides were exported and printed, and preoperative simulations using a replica of the patient's skull established the sequence of steps. The accuracy of the procedure was evaluated postoperatively using computed tomography (CT) scans. Results: In every patient examined, the all-in-one surgical-guide system was able to automate the many steps in the procedure and dramatically decreased the duration of surgery. The experimental guide enhanced every phase of surgery, including excising the lesion, and harvesting, positioning, and fixing the graft. In each step, precision was enhanced and the outcome corresponded with the VSP. Conclusions: The few previous reports on cutting guides used in cranioplasty generally describe the use of separate guides for dismantling and reconstruction. The ability to perform more surgical sequences using a single tool can improve surgical accuracy. Clearly there is no single perfect surgical guide; however, effective surgical-design strategies should be used to build the best approach to each procedure.